MANDATORY WILL IN KHI REGARDING THE INHERITANCE OF ADOPTED CHILDREN ACCORDING TO JAVANESE SOCIETY - Ashari, Beni; Wahyudi, Imam (STAI Nurul Huda Kapongan Situbondo, 2023)
Inheritance is the distribution of property from one generation to the nex. But it can’t be called comprehensively considering the problem of inheritance has its own problems so that adoption of children in kandangtepus village makes inheritance into consideration. There are several factors that cause inheritance to adopted children. Sometimes children get inheritance and sometimes only get paid for the purchase school fees. It was decided by family deliberation. In this study, the subject of this research is the javanese people who adopt children. With using a qualitative (field reseach) approach and the type of phenomenological reseach. This study resulted in: 1) adopted children still get the inheritance. Because of the human factor. 2) there are two divisions of inheritance between biological children and adopted children, some are equated because they are like their own children, and some are through inheritance grants or wills. 3) the result of inheritance of the adopted cjild does not occur, because it has been discussed in advance.